2017
DOI: 10.1016/j.psychres.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Is heart rate variability (HRV) an adequate tool for evaluating human emotions? – A focus on the use of the International Affective Picture System (IAPS)

Abstract: Because human emotion varies greatly among individuals and is a qualitative factor, measuring it with any degree of accuracy is very difficult. Heart rate variability (HRV), which is used in evaluations of the autonomic nervous system (ANS), is used to evaluate human emotions. This study examines the validity of HRV as a tool to evaluate emotions using the International Affective Picture System (IAPS). For experimentation, five photos were selected for each of the categories of "happy," "unhappy", and "neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 22 publications
2
77
1
8
Order By: Relevance
“…It is already documented that RRI is associated with the condition of one's automatic nervous system, representing emotional status. Choi et al [52] provided evidence that heart rate variability could be used to adequately evaluate human emotion. Valenza, Antonio, and Enzo [53] and Lane et al [54] also confirmed that heart rate variability could be an objective tool to assess emotional responses.…”
Section: Sample Selection Variable Definitions and Measurement Issuesmentioning
confidence: 99%
“…It is already documented that RRI is associated with the condition of one's automatic nervous system, representing emotional status. Choi et al [52] provided evidence that heart rate variability could be used to adequately evaluate human emotion. Valenza, Antonio, and Enzo [53] and Lane et al [54] also confirmed that heart rate variability could be an objective tool to assess emotional responses.…”
Section: Sample Selection Variable Definitions and Measurement Issuesmentioning
confidence: 99%
“…HRV (heart rate variability) is a method that has been widely used in the academic literature. It reflects the state of ANS (autonomic nervous system) [28]. It is therefore a good objective tool for assessing emotional responses [29].…”
Section: Heart Ratementioning
confidence: 99%
“…For some research based on contexts like emotion recognition based on physiological data, it is not recommended to use only one data e.g., heart rate variability, to accurately detect emotions, because it can reflect emotions only in strong or intense emotional situations [25]. According to some studies, when an extended number of physiological data are considered, better results can be reached.…”
Section: Proposed Multimodal Sensing Systemmentioning
confidence: 99%